Pre-stimulation of precision-cut bovine udder slices with zymosan before LPS exposure indicates aspects of trained immunity especially in the absence of FCS - Viviane Filor; Joanna Myslinska; Amitis Saliani; Jesmond Dalli; Peter Olinga; Wolfgang Bäumer; Dirk Werling (Innate Immunity)
Mastitis in cattle poses a significant health challenge and results in substantial economic losses for the dairy industry. This study aimed to extend the existing precision-cut bovine udder slices (PCBUS) model as an in vitro model to explore the potential of inducing trained immunity in the udder with the goal to use the resulting knowledge for potential new treatment strategies. Interestingly, incubation of PCBUS with 10% fetal calf serum (FCS), but no 2% or FCS-free, negatively affected the production of some of the chemokines/cytokines analysed. When trained immunity was induced by zymosan, followed by stimulation with E. coli -derived lipopolysaccharide (LPS), production of interleukin (IL)-1β, IL-6, tumor necrosis factor α and interferon (IFNγ) was downregulated while production of IL-17A and pro-resolving lipid mediators (leukotrienes and prostaglandins) was upregulated. While the current experimental setup did not definitively confirm the induction of trained immunity for all parameters analysed in PCBUS, it validated the utility of PCBUS as a robust in vitro model for studying bovine udder inflammation. This model offers a promising platform for developing innovative mastitis treatments, particularly given the growing concern over antimicrobial resistance, as well as offering alternatives to the use of live animals in experimental studies in line with the 3Rs principles. It also provides a valuable tool for advancing our understanding of immune responses in the bovine udder. By adapting the precision-cut tissue slice technique to bovine udders, this model enables extensive research into new therapeutic approaches and supports basic research efforts to characterise complex pathophysiological processes associated with mastitis. Furthermore, our data highlight the potential limitations of FCS in in vitro studies. Our data should not only stimulate the discussion about FCS in homologues or heterologues species, but should also be kept in mind regarding the need for foetal calves to generate FCS in line with the 3Rs guideline.